EVOLUTION OF THE SPIN OF LATE-TYPE GALAXIES CAUSED BY GALAXY–GALAXY INTERACTIONS - 황정선; 박창범; 남수현; 정해은 (Journal of the Korean Astronomical Society, 54(2), 2021)
We use N-body/hydrodynamic simulations to study the evolution of the spin of a Milky Way-like galaxy through interactions. We perform a controlled experiment of co-planar galaxy-galaxy encounters and study the evolution of disk spins of interacting galaxies. Specifically, we consider cases where the late-type target galaxy encounters an equally massive companion galaxy, which has either a late or an early-type morphology, with a closest approach distance of about 50 kpc, in prograde or retrograde sense. By examining the time change of the circular velocity of the disk material of the target galaxy from each case, we find that the target galaxy tends to lose the spin through prograde collisions but hardly through retrograde collisions, regardless of the companion galaxy type. The decrease of the spin results mainly from the deflection of the orbit of the disk material by tidal disruption. Although there is some disk material which gains the circular velocity through hydrodynamic as well as gravitational interactions or by transferring material from the companion galaxy, it turns out that the amount of the material is generally insufficient to increase the overall galactic spin under the conditions we set. We find that the spin angular momentum of the target galaxy disk decreases by 15-20% after a prograde collision. We conclude that the accumulated effects of galaxy-galaxy interactions will play an important role in determining the total angular momentum of late-type galaxies. KCI Citation Count: 2